2019
DOI: 10.1186/s40425-019-0641-x
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Maraba virus armed with tumor antigen boosts vaccine priming and reveals diverse therapeutic response patterns when combined with checkpoint blockade in ovarian cancer

Abstract: Background Cancer immunotherapies are emerging as promising treatment strategies for ovarian cancer patients that experience disease relapse following first line therapy. As such, identifying strategies to bolster anti-tumor immunity and limit immune suppression, while recognizing diverse patterns of tumor response to immunotherapy is critical to selecting treatment combinations that lead to durable therapeutic benefit. Methods Using a pre-clinical mouse model, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 66 publications
(66 reference statements)
1
54
0
Order By: Relevance
“…The present study suggests that measles vaccines can also be designed to promote CTL responses against specific tumor antigens by encoding the antigens or their immunodominant epitopes in the viral vector. Other oncolytic virus platforms, such as VSV and Maraba virus, have been used for this purpose [24][25][26][27][28]30,64]. Though not effective as a priming vector, Maraba viruses encoding tumor antigens have been shown to efficiently boost CTL-mediated anti-tumor immunity by infection of splenic follicular B cells [29,65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study suggests that measles vaccines can also be designed to promote CTL responses against specific tumor antigens by encoding the antigens or their immunodominant epitopes in the viral vector. Other oncolytic virus platforms, such as VSV and Maraba virus, have been used for this purpose [24][25][26][27][28]30,64]. Though not effective as a priming vector, Maraba viruses encoding tumor antigens have been shown to efficiently boost CTL-mediated anti-tumor immunity by infection of splenic follicular B cells [29,65].…”
Section: Discussionmentioning
confidence: 99%
“…As another approach to direct the immune response against the tumor, oncolytic viruses encoding tumor antigens have been developed [24][25][26][27][28][29][30][31]. Different antigen expression strategies have been realized in recombinant viral vectors for tumor vaccination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to increase the abundance of tumor antigens would be to use an OV armed with a tumor antigen. A recent study by McGray et al demonstrated the feasibility of such an approach to boost vaccine priming and increase overall therapeutic response in an ovarian cancer model [113]. The authors used a Maraba virus encoding full-length ovalbumin (OVA) as a tumor antigen to treat a murine ovarian tumor model engineered to express OVA.…”
Section: Tumor Antigensmentioning
confidence: 99%
“…Human monocyte-derived macrophage Maraba exposure: The attenuated strain MG1 Maraba virus has been previously described (Brun et al, 2010;Pol et al, 2014). Maraba virus was prepared and titered at McMaster University, shipped on dry ice to RPCCC, stored at − 80 °C and used as described (McGray et al, 2019).…”
Section: Viral Infectionsmentioning
confidence: 99%